2017
DOI: 10.1002/bip.22935
|View full text |Cite
|
Sign up to set email alerts
|

Homooligomeric β3(R)‐valine peptides: Transformation between C14 and C12 helical structures induced by a guest Aib residue

Abstract: Novel helical, structures unprecedented in the chemistry of α-polypeptides, may be found in polypeptides containing β and γ amino acids. The structural characterization of C and C -helices in oligo β-peptides was originally achieved using conformationally constrained cyclic β-residues. This study explores the conformational characteristics of proteinogenic β residues in homooligomeric sequences and addresses the issue of inducing a transition between C and C helices by the introduction of a guest α-residue. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While the population and nature of folded, intramolecularly hydrogen‐bonded conformations may differ under the two distinct solvent conditions, 20%, v/v DMSO:CDCl 3 and CD 3 OH, it is clear that the 12‐residue peptide upon disaggregation tends to fold, resulting in shielding from solvent of most of the backbone NH groups. In a previous study, we had demonstrated folding into a 14‐helical structure for the related 9‐residue peptide, based upon hydrogen bonding data together with nuclear Overhauser effects (NOEs) . It is thus reasonable to suggest that further extension of the β 3 (R)‐Val chain does indeed lead to extension of the helical structure.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…While the population and nature of folded, intramolecularly hydrogen‐bonded conformations may differ under the two distinct solvent conditions, 20%, v/v DMSO:CDCl 3 and CD 3 OH, it is clear that the 12‐residue peptide upon disaggregation tends to fold, resulting in shielding from solvent of most of the backbone NH groups. In a previous study, we had demonstrated folding into a 14‐helical structure for the related 9‐residue peptide, based upon hydrogen bonding data together with nuclear Overhauser effects (NOEs) . It is thus reasonable to suggest that further extension of the β 3 (R)‐Val chain does indeed lead to extension of the helical structure.…”
Section: Resultsmentioning
confidence: 92%
“…In Boc‐protected peptides, the N‐terminus, NH resonance appears at higher field than the remaining backbone NH groups and is readily assigned. Assignment of the remaining resonances may be achieved by a combination of TOCSY and NOESY experiments as described in our earlier report for the 9‐residue peptide . However, in homo‐oligomeric sequences extensive resonance overlap of the backbone protons of the β‐residues can render unambiguous assignment difficult with increasing peptide chain length.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations